PCDH10 is a candidate tumour suppressor gene in medulloblastoma - Bertrand, Kelsey C.; Mack, Stephen C.; Northcott, Paul A.; Garzia, Livia; Dubuc, Adrian; Pfister, Stefan; Rutka, James T.; Weiss, William A.; Taylor, Michael D. (Child's nervous system, 2011)
The aim of this study was to investigate the genetic and epigenetic mechanisms contributing to PCDH10 down-regulation in medulloblastoma. We examined the role of PCDH10 as a mediator of medulloblastoma cell proliferation, cell cycle progression, and cell migration.
Gesehen am 23.03.2022